Efficacy and safety of Atractylodes macrocephala-containing traditional Chinese medicine combined with neoadjuvant chemotherapy in the treatment of advanced gastric cancer: a systematic evaluation and meta-analysis - Niu, Xiaotao; Gu, Haoqing; Li, Jingzhan; Zuo, Jiaqian; Ren, Wenqin; Huang, Yujie; Shu, Xinyan (Frontiers in Oncology, 2024)
BackgroundIn China, Atractylodes-containing Chinese medicines are widely used as adjuvant therapy to neoadjuvant chemotherapy (NAC) in individuals diagnosed with advanced gastric cancer (AGC). Nevertheless, the findings concerning its effectiveness are still restricted. The aim from this research was to examine the efficiency and security Atractylodes macrocephala-containing traditional Chinese medicine together with NAC in the management of AGC.MethodsLiterature was systematically searched across 8 electronic databases until September 20, 2023. Two researchers conducted a thorough review of the selected studies. The primary outcome measures included the objective response rate (ORR), disease control rate (DCR), quality of life (QOL), adverse drug reactions (ADRs), and levels of peripheral blood lymphocytes. The relevant effect estimates are as follows as risk ratios (RR) or mean differences (MD) with corresponding 95% confidence intervals (CI). Credibility of information was evaluated using the GRADE analyzer.ResultsThe results showed that solely on the basis of the accessible literature examined in NAC patients, individuals who received the therapeutic regimen containing Atractylodis Macrocephalae Chinese herbal preparations demonstrated a superior overall response rate (Relative Risk: 1.41, 95% confidence interval: 1.27-1.57, P < 0.001); DCR (RR: 1.20, 95% confidence interval: 1.13-1.27, P < 0.001), as compared to QOL (RR: 1.43, 95% confidence interval: 1.30-1.57, P < 0.001, MD: 8.47, 95% confidence interval: 7.16 - 9.77, P < 0.001); the proportions of CD3+ T-cells, CD4+ T-cells, CD8+ T-cells, CD4+CD8+ T-cells were increased; and the incidence of adverse reactions was decreased. Subgroup analyses showed that oral administration of all the traditional Chinese medicines containing Atractylodes macrocephala could improve tumor efficacy. Regardless of the duration of therapy of ≥8 weeks or <8 weeks, Atractylodes macrocephala-containing traditional Chinese medicine increased the tumor response in AGC patients. Combination of Atractylodes macrocephala-containing TCM with neoadjuvant chemotherapy increased ORR and DCR; when used in conjunction with cisplatin, only ORR was increased.ConclusionThe combination of Atractylodes macrocephala-containing herbs with NAC in the treatment of AGC improves efficacy, improves prognosis, and reduces adverse effects. Nevertheless, additional high-quality randomized trials are required.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023461079.